How abnormal is the normal? Clinical characteristics of CF patients with normal FEV1. Issue 7 (26th March 2021) - Cohen‐Cymberknoh, Malena; Ben Meir, Elad; Gartner, Silvia; Reiter, Joel; Spangenberg, Angeles; Garriga, Laura; Eisenstadt, Iris; Israeli, Tomer; Tsabari, Reuven; Shoseyov, David; Gileles‐Hillel, Alex; Breuer, Oded; et al.
Abstract: Background: Normal values (>80%) of Forced Expiratory Volume in one second (FEV1 ) in patients with cystic fibrosis (CF) may lead to the interpretation that there is no lung disease. This study is a comprehensive analysis of lung involvement in CF patients having normal FEV1 . Methods: Patients were recruited from two CF centers: Hadassah Medical Center, Jerusalem and Vall d' Hebron Hospital, Barcelona. Lung disease was assessed by lung clearance index (LCI), chest CT‐Brody score, respiratory cultures, number of pulmonary exacerbations (PEx), and days of antibiotic treatment in the year before the assessment. Results: Of the 247 patients, 89 (36%) had FEV1 ≥80% and were included in the study (mean age, 17.6; range, 4.25–49 years). Chronic Pseudomonas aeruginosa infection was found in 21%, and 31% had at least one major PEx in the year before the study. Abnormally elevated LCI was found in 86% of patients, ranging between 7.52 and 18.97, and total Brody score (TBS) was abnormal in 92% (range, 5.0–96.5). Patients with chronic P. aeruginosa had significantly higher LCI ( p  = .01) and TBS ( p  = .02) which were associated with more major PEx ( p  < .01 and p  = .01, respectively) and more days of intravenous (IV) antibiotic treatment in the preceding year ( p  = .03 and p  = .001, respectively). Conclusions: Most CF patients with normal FEV1 have already physiological and structural lung abnormalities which were associated with more PEx and IV antibiotic treatment. Further studies are needed to determine if better adherence to the currently used therapies and the new cystic fibrosis transmembrane modulators will prevent the progression of lung disease.